History of health care development in the Republic of Kazakhstan - Baizhiyenova, K.; Janguzhiyev, M.; Baibulsinova, A.; Serikova, L.; Zhalekenova G. (Salud, Ciencia y Tecnologia, 2024)
Introduction: The urgent need to modernize Kazakhstan’s healthcare system arises from deep-rooted economic crises and systemic challenges exacerbated during the transition to capitalism from Soviet-era centralized planning. Objective: The research aims to analyze the stages of development of healthcare in the Republic of Kazakhstan since the country gained its independence. Methods: To solve the set tasks the authors applied such methods of knowledge as historical, comparative, systemic, and method of political-legal analysis. Results: Research results consist in the formulation of the basic stages of development of public health in Kazakhstan, the definition of advantages and disadvantages of functioning of the given branch on each of them, and also in the designation of transformations and innovations in the public health sphere for last years. Conclusions: The materials of this research can be applied in the applied and research spheres. In particular, the research may be of interest to the employees of the state authorities who are dealing with the problems of reforming the health care system in post-Soviet countries. In addition, the materials can be used in the work of scientists whose sphere of interest includes the formation of policy in the field of health care managemen Острая необходимость модернизации системы здравоохранения Казахстана обусловлена глубоко укоренившимися экономическими кризисами и системными проблемами, обострившимися во время перехода к капитализму от централизованного планирования советской эпохи. Цель: исследование направлено на анализ этапов развития здравоохранения в Республике Казахстан с момента обретения страной независимости. Методы: Для решения поставленных задач авторы применили такие методы познания, как исторический, сравнительный, системный, метод политико-правового анализа. Результаты: Результаты исследования заключаются в формулировке основных этапов развития здравоохранения в Казахстане, определении преимуществ и недостатков функционирования данной отрасли на каждом из них, а также в обозначении преобразований и инноваций в здравоохранении. сфере за последние годы. Выводы: Материалы исследования могут быть применены в прикладной и исследовательской сферах. В частности, исследование может быть интересно работникам органов государственной власти, занимающимся проблемами реформирования системы здравоохранения в странах постсоветского пространства. Кроме того, материалы могут быть использованы в работах ученых, в сферу интересов которых входит формирование политики в области управления здравоохранением.
History of health care development in the Republic of Kazakhstan / K. Baizhiyenova, M. Janguzhiyev, A. Baibulsinova, L. Serikova, G. Zhalekenova. - Текст : непосредственный // Salud, Ciencia y Tecnologia. - 2024. - Vol. 41. - Р. 1-10 (Scopus). - ISSN 2796-9711.
Keywords: doi 10.56294/saludcyt2024.577; импакт-фактор 2024; scopus; здравоохранение казахстана; модернизация здроавоохранения; government program; health care; health care system; medical care; modernization; reform; периодическое издание; РК